1994
DOI: 10.1093/ajcn/59.4.879
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the acute effects of resistant starch and dietary fibers on metabolic indexes in men

Abstract: The effect of ingestion of the same amount (30 g) of a resistant starch (lintner) and cellulose on energy expenditure (EE), colonic fermentation (breath-hydrogen test), and blood glucose, insulin, and free fatty acid (FFA) concentrations were compared in seven healthy volunteers in a first experiment. In a second experiment the same indexes were measured in six healthy volunteers after the ingestion of diets composed of 50 g glucose alone or mixed with 30 g lintner, or cellulose, or pectin. In the first experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 17 publications
3
33
0
Order By: Relevance
“…However, little evidence supported this hypothesis and several studies have failed to show that RS increases energy expenditure or fat oxidation [29][30][31]. Although previous reports also showed that the improvement in blood cholesterol and triglyceride levels might be related to the reduced blood glucose levels in the diabetic rats [32,33], it is still an unconfirmed hypothesis until now.…”
Section: Discussionmentioning
confidence: 99%
“…However, little evidence supported this hypothesis and several studies have failed to show that RS increases energy expenditure or fat oxidation [29][30][31]. Although previous reports also showed that the improvement in blood cholesterol and triglyceride levels might be related to the reduced blood glucose levels in the diabetic rats [32,33], it is still an unconfirmed hypothesis until now.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that eating a diet rich in RS may increase the mobilization and use of fat stores as a direct result of a reduction in insulin secretion (Tapsell, 2004). Studies to date in humans would indicate that diets rich in RS do not affect total energy expenditure, carbohydrate oxidation or fat oxidation (Ranganathan et al, 1994;Tagliabue et al, 1995;Howe, Rumpler, & Behall, 1996;Raben et al, 1997). In another study on human volunteers, breads rich in RS imparted greater satiety than white breads between 70 and 120 min after eating (De Roos, Heijnen, & De Graff, 1995).…”
Section: Inhibition Of Fat Accumulationmentioning
confidence: 99%
“…Urinary C peptide excretion did only show a moderate reduction, but in contrast to the recently seen unresponsiveness of urinary and circulating DHEAS to a similar C peptide decrease (29), an additional nutritional factor known to affect the insulin secretory dynamics was effective in the present study. This factor was dietary fiber intake that along with protein intake showed the strongest percent difference between diet L and diet N. A decrease in protein intake per se reduces insulin secretion (29,37), and an increased fiber (especially pectin) intake further attenuates postmeal insulin secretory peaks (38,39). Integrated insulin secretion, i.e.…”
Section: Table 2 Urinary 24-h Excretion Rates Of 17-kss C Peptidementioning
confidence: 99%
“…Integrated insulin secretion, i.e. urinary 24-h C peptide output, is not necessarily affected by this insulin peak-flattening effect of fiber, because an altered postprandial plasma dynamics with a slowed glucose and insulin decline can be present (38). Thus, if insulin is actually involved in the modulation of adrenocortical activity as suggested here, the sole variation of only one potent dietary insulin secretagogue [with definitely stronger effects on C peptide excretion, as recently described (29)] should also produce significant changes in urinary cortisol and DHEAS excretion.…”
Section: Table 2 Urinary 24-h Excretion Rates Of 17-kss C Peptidementioning
confidence: 99%